Resolvin D1 Improves the Treg/Th17 Imbalance in Systemic Lupus Erythematosus Through miR-30e-5p - Cheng, Tao; Ding, Shuai; Liu, Shanshan; Li, Xiaojing; Tang, Xiaojun; Sun, Lingyun (Frontiers in Immunology, 2021)
Resolvin D1 (RvD1) prompts inflammation resolution and regulates immune responses. We explored the effect of RvD1 on systemic lupus erythematosus (SLE) and investigated the correlation between RvD1 and Treg/Th17 imbalance, which is one of the major factors contributing to the pathogenesis of disease. SLE patients and healthy controls were recruited to determine plasma RvD1 levels. MRL/lpr lupus model was used to verify rescue of the disease phenotype along with Treg/Th17 ratio. Purified naive CD4+ T cells were used to study the effect of RvD1 on Treg/Th17 differentiation in vitro. Furtherly, small RNA Sequencing and transfection were performed successively to investigate downstream microRNAs. The result showed that the RvD1 level was significantly lower in active SLE patients compared with inactive status and controls. Moreover, The SLE disease activity index (SLEDAI) score had a significant negative correlation with RvD1 level. As expected, RvD1 treatment ameliorated disease phenotype and inflammatory response, improved the imbalanced Treg/Th17 in MRL/lpr mice. In addition, RvD1 increased Treg while reduced Th17 differentiation in vitro. Furthermore, miR-30e-5p was verified to modulate the Treg/Th17 differentiation from naïve CD4+ T cells as RvD1 downstream microRNA. In conclusion, RvD1 effectively ameliorates SLE progression through up-regulating Treg and down-regulating Th17 cells via miR-30e-5p.